1987
DOI: 10.1161/01.cir.75.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after the Fontan operation for tricuspid atresia.

Abstract: Between 1968 and 1977, 32 patients who underwent the Fontan operation for tricuspid atresia at Bordeaux, France, or Leiden, The Netherlands, survived at least 1 year after surgery. These patients were evaluated clinically 7 to 16 years (mean 8.9 years) after surgery by review of clinical records, questionnaire, or direct examination. There were five deaths: one during arrhythmia, the second sudden and unexplained, and three others after reoperation. Four of the five patients had evidence of obstruction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…[11][12][13][14][15][16][17] The occurrence of SVTA after the modified Fontan operation has been reported to range from 20% to 37.5% in follow-up periods of up to 15 years. 12,24 In the present study, the late occurrence of SVTA at 5 years after the operation was 17%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] The occurrence of SVTA after the modified Fontan operation has been reported to range from 20% to 37.5% in follow-up periods of up to 15 years. 12,24 In the present study, the late occurrence of SVTA at 5 years after the operation was 17%.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, the development of late-onset supraventricular tachyarrhythmias (SVTAs) continues to be a problem. [11][12][13] Various investigators 8,[13][14][15][16][17] have postulated that by altering the surgical technique one may decrease the incidence of SVTA.…”
mentioning
confidence: 99%
“…Incisional atrial re-entrant tachycardia (IART) is a lifethreatening complication that occurs after repair of congenital heart defects (Girod et al, 1987). This tachycardia is often medically refractory (Balaji et al, 1994).…”
Section: Incisional Atrial Re-entrant Tachycardia After Surgery For Cmentioning
confidence: 99%
“…This tachycardia is often medically refractory (Balaji et al, 1994). The incidence of IART has been found to be 20-38% in patients followed late after the Fontan procedure (Girod et al, 1987;Porter and Garson, 1993). In patients who have undergone atrial septal defect repair, it has been shown that 4-18% of patients experience this tachycardia during a 10-to 32-year follow-up period (Murphy et al, 1990).…”
Section: Incisional Atrial Re-entrant Tachycardia After Surgery For Cmentioning
confidence: 99%
“…1) Studies mainly of pediatric patients have reported atrial tachyarrhythmias in up to 57% of patients who have undergone the Fontan procedure. [2][3][4][5][6][7][8][9][10] Recent electrophysiological studies including three-dimensional electroanatomical mapping (CARTO Ò ) and noncontact mapping (EnSite 3000 Ò ) have shown that 88-100% of the atrial tachycardias (ATs) that occur after surgical repair of congenital heart disease are macroreentrant ATs. [11][12][13][14] This report describes the case of a 28-years-old woman who had undergone the Fontan procedure as a child for tricuspid atresia and in whom focal AT developed 22 years after the procedure.…”
Section: Introductionmentioning
confidence: 99%